The role of lenders´ geographical diversification in P2P transactinos - Maria, Edoardo Di (2020)
In this dissertation,I provide novel evidenceof the impact of geographical diversification on loan interest rates. The findings, based on a unique dataset of all P2P transactions in a UK platformover the period 2010-2013, suggest that more geographically-diversified lenders are more likely to impose lower interest rates in their contract terms in P2P transactions, while more concentrated lenders (in terms of geographical concentration of the activities) practice higher loan interests rate. These results are robust to an alternative econometric approach.